Name and Characteristics of National Institutes of Health R01-Funded Pediatric Physician-Scientists: Hope and Challenges for the Vanishing Pediatric Physician-Scientists - Good, Misty (JAMA Pediatr, 2018)
This study describes the number and characteristics of physician-scientists who are funded by National Institutes of Health independent investigator awards.